An app for fishers: The University of the West Indies' multifunctional mFisheries app - Mallalieu, Kim I.; Suraj, Amanda (Technical Centre for Agricultural and Rural Cooperation, 2017)
A mobile application called mFisheries was developed by the Department of Electrical and Computer Engineering at the University of the West Indies with support from development agencies such as the International Development Research Centre (IDRC) and the Technical Centre for Agricultural and Rural Cooperation (CTA). To use the app, fishers need a smartphone with global positioning capabilities. While the app will work on any suitable Android phone, it is best to have one that is waterproof and shock-resistant so it can survive the knocks and splashes that are unavoidable on a pitching boat. The mFisheries team recommends phones such as the RugGear RG600 which have large screens, a long battery life and rugged construction.